A Systematic Approach to Incision Planning and Graft Excision in Gender-affirming Vaginoplasty. Issue 2 (15th February 2022) - Dy, Geolani W.; Butler, Christi; Peters, Blair; Dugi, Daniel D.
Abstract : Summary: We present our systematic approach to incision planning and skin graft excision for gender-affirming vaginoplasty. This approach is adaptable to patients of different body habitus and genital skin surface area, and it allows for early skin graft harvest with predictable wound tension at closure. We also describe how to adapt in cases of severe genital hypoplasia.